An unusual case of ptosis - K, Abhilash (International Journal of Research in Medical Sciences, 2017)
Blepharophimosis is a condition where the patient has bilateral ptosis with reduced lid size, vertically and horizontally. The nasal bridge is flat and there is hypoplastic orbital rim. Here I am presenting a case of a father & son with blepahrophimosis which could be a part of an uncommon condition called BPES (Blepharophimosis, Ptosis, Epicanthus Inversus, Telecanthus).